COMBINED MITRAL AND TRICUSPID STENOSIS IN 47-YEAR OLD RHEUMATIC VALVULAR HEART DISEASE PATIENT: A CASE REPORT - Ejeagba OO; Ayoola YA; Ejeh AB; Adamu A; Okolie HI; Danbauchi SS (Ntec Specialist, 2020)
Background: Rheumatic valvular heart disease is a common complication of rheumatic fever; however combined mitral and tricuspid stenosis is an extremely rare form of multi-valve disease presentation. Case Presentation: We report a case of combined mitral and tricuspid stenosis from rheumatic heart disease (RHD) in a 47-year-old woman who was being managed for hypertensive heart disease (HHDx) on anti-hypertensives for 2yrs prior to presentation. However, on further review with transthoracic echocardiography (TTE), she was found to have thickened mitral valve and hockey stick appearance with dilated left atrium (dimension of 60mm) and reduced left ventricular ejection fraction (LVEF) of 45%. A repeat TTE done 8 years after the first one showed a severely dilated left atrium (LAD 71mm) with estimated area of 55.4cm2; moderate mitral stenosis and severe tricuspid stenosis with moderate TR. The LVEF was 29% with a severe right ventricular (RV) systolic dysfunction (TAPSE of 9mm). Patient is being managed conservatively due to economic constraints and the likelihood of very poor surgical outcome due to severe biventricular dysfunction. Conclusion: The case is reported for its rarity as well as the importance of interval evaluation of unaffected valves in a setting of single valve disease for early detection and possible prompt treatment and intervention.